Actions do not speak louder than words in an interactive false belief task. Issue 10 (14th October 2020) - Wenzel, Lisa; Dörrenberg, Sebastian; Proft, Marina; Liszkowski, Ulf; Rakoczy, Hannes
Abstract : Traditionally, it had been assumed that meta-representational Theory of Mind (ToM) emerges around the age of 4 when children come to master standard false belief (FB) tasks. More recent research with various implicit measures, though, has documented much earlier competence and thus challenged the traditional picture. In interactive FB tasks, for instance, infants have been shown to track an interlocutor's false or true belief when interpreting her ambiguous communicative acts (Southgate et al . 2010 Dev. Sci. 13, 907–912. (doi:10.1111/j.1467-7687.2009.00946.x )). However, several replication attempts so far have produced mixed findings (e.g. Dörrenberg et al . 2018 Cogn. Dev. 46, 12–30. (doi:10.1016/j.cogdev.2018.01.001 ); Grosse Wiesmann et al. 2017 Dev. Sci. 20, e12445. (doi:10.1111/desc.12445 ); Király et al . 2018 Proc. Natl Acad. Sci. USA 115, 11 477–11 482. (doi:10.1073/pnas.1803505115 )). Therefore, we conducted a systematic replication study, across two laboratories, of an influential interactive FB task (the so-called 'Sefo' tasks by Southgate et al . 2010 Dev. Sci. 13, 907–912. (doi:10.1111/j.1467-7687.2009.00946.x )). First, we implemented close direct replications with the original age group (17-month-olds) and compared their performance to those of 3-year-olds. Second, we designed conceptual replications with modifications and improvements regarding pragmatic ambiguities for 2-year-olds. Third, we validated the task with explicit verbal test versions in older children and adults. Results revealed the following: the original results could not be replicated, and there was no evidence for FB understanding measured by the Sefo task in any age group except for adults. Comparisons to explicit FB tasks suggest that the Sefo task may not be a sensitive measure of FB understanding in children and even underestimate their ToM abilities. The findings add to the growing replication crisis in implicit ToM research and highlight the challenge of developing sensitive, reliable and valid measures of early implicit social cognition.